Identity(ies): a multicultural and multidisciplinary approach - Ana Paula Arnaut (Coimbra University Press, 2017)
At a time when the world watches in horror the unfolding drama of millions of refugees and the anxiety of identity figures prominently among globalization$1 (Bs many side effects, this is certainly a very timely book, with contributions that address the momentous issues at hand in ways that are not just varied but also surprisingly illuminating.It seems only appropriate that the book starts and ends ((3z(BWhoever is not Greek is a barbarian(3y(B; (3z(BThe Women of the Other and us(3y(B) with well contextualized, historical / theoretical reflexions on the unfailingly self-serving construction and ultimate appropriation of (3z(Bthe other(3y(B, be it the supposedly inarticulate savage of neighboring barbarian shores or the haunting background presence of Arab women - the barely acknowledged half of the West$1 (Bs reified (3z(BRest(3y(B. ln fact, although the chronological distance between the two historical moments is such as to discourage hasty generalizations, the continuities and the potential relevance are just too striking to be ignored. s
Portuguese
Keywords: Portuguese